Training Evaluation Based on the Kirkpatrick Levels 2 and 3 Evaluation Model: A Case Study on Induction Program for Novice Teachers - Larasati, Agnes; Asropi, Asropi (Jurnal Borneo Administrator, 2025)
The 2021 Teacher Competency Test results indicate the need to enhance teacher competency. The Novice Teachers Induction Program is designed to address this issue by guiding new teachers in their professional development. This research aims to evaluate the induction program results for Novice Teachers regarding teacher competence development using the Kirkpatrick Levels 2 and 3 training evaluation models. This seeks to determine the impact of the induction program on the development of skills and knowledge and the changes in attitudes and behavior of novice teachers. This research employed a qualitative descriptive research design,with a case study regarding implementing the induction program for Novice Teachers at at one of the public junior high schools in Jakarta, Indonesia. Data collection was done through interviews, document analysis, and observation. Based on the evaluation results using the Kirkpatrick Levels 2 and 3 evaluation model, it was found that the induction program positively impacted competency development, increased knowledge, improved skills, and changed the attitudes and behavior of Novice Teachers. The supervisors also succeeded in overcoming the challenges faced by Novice Teachers. However, the induction programs for Novice Teachersrequired more explicit formative assessment instruments. In evaluating the performance of Novice Teachers, they only relied on observations from supervising teachers, school principals, and supervisors. Recommendations were therefore provided to the Directorate General of Teachers and Education Personnel to reform implementation standards and performance assessment instruments within the PIGP